2017
DOI: 10.15406/jaccoa.2017.07.00285
|View full text |Cite
|
Sign up to set email alerts
|

Breast Augmentation: Reducing Postoperative Nausea and Vomiting. A Prospective Study

Abstract: Background: Breast augmentation is the plastic surgery procedure associated with the greatest risk of postoperative nausea and vomiting (PONV). The purpose of this study is to evaluate the efficacy of a specific antiemetic protocol applied in breast augmentation in order to diminish the incidence of PONV Methods: A prospective-level of evidence II-study was performed in 247 patients that underwent breast augmentation from October 2010 to October 2014. General anesthesia was induced with propofol, fentanyl and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(41 reference statements)
0
0
1
Order By: Relevance
“…No subjects experienced delayed hospital discharge, remained in the hospital after surgery due to PONV or were admitted after discharge due to delayed PONV (DPONV). The overall and between-group incidence of PONV in this study is lower than the prevalence reported in recent literature for ambulatory surgery ( 49 , 50 ) and specifically for breast surgery ( 35 , 45 , 51 , 52 ). The fact that opioid consumption in our study was comparable between groups most likely did not allow for a significant inter-group difference in PONV.…”
Section: Discussioncontrasting
confidence: 78%
“…No subjects experienced delayed hospital discharge, remained in the hospital after surgery due to PONV or were admitted after discharge due to delayed PONV (DPONV). The overall and between-group incidence of PONV in this study is lower than the prevalence reported in recent literature for ambulatory surgery ( 49 , 50 ) and specifically for breast surgery ( 35 , 45 , 51 , 52 ). The fact that opioid consumption in our study was comparable between groups most likely did not allow for a significant inter-group difference in PONV.…”
Section: Discussioncontrasting
confidence: 78%